Enhancing emulsified sausages: a comprehensive study of the nutritional, sensory, and sustainability advantages of quinoa flour incorporation - Assel Dautova; Kumarbek Amirkhanov; Sholpan Baytukenova; Gulnur Nurymkhan; Zhanna Assirzhanova; Zhibek Atambayeva; Saule Baytukenova; Rysgul Ashakayeva; Aray Kambarova (Cogent Food & Agriculture)
This study investigates the use of quinoa flour (QF), in both dry (WQF) and hydrated (HWQF) forms, as an innovative ingredient in emulsified sausage formulations. The focus is on its influence on physicochemical aspects, oxidative stability, sensory qualities, and nutritional value. HWQF-enhanced emulsions exhibited exceptional water-holding capacities (82.56%) compared to WQF (79.84%) and control samples (53.45%). Quinoa flour also improved emulsion stability, indicated by reduced expressible fluid and fat. PCA analysis showed that quinoa positively impacted taste, texture, juiciness, and overall acceptability, particularly in HWQF sausages, without significantly altering the fatty acid profile. The study underscores quinoa’s potential as a health-promoting and sustainable meat binder alternative. Future research directions include assessing long-term storage effects, consumer acceptance, and the impact of different quinoa varieties, aiming to enhance the commercial and environmental appeal of quinoa-enriched meat products for health-conscious markets.